2022
DOI: 10.1007/s10495-022-01754-9
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 causes neuronal degeneration and reduces neurogenesis in human hippocampus

Abstract: Recent investigations of COVID-19 have largely focused on the effects of this novel virus on the vital organs in order to efficiently assist individuals who have recovered from the disease. In the present study we used hippocampal tissue samples extracted from people who died after COVID-19. Utilizing histological techniques to analyze glial and neuronal cells we illuminated a massive degeneration of neuronal cells and changes in glial cells morphology in hippocampal samples. The results showed that in hippoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 106 publications
2
28
0
Order By: Relevance
“…Based on previous results indicating that variation of monocytes to total leukocytes is predictive of anosognosia in the chronic phase (Nuber-Champier, 2022), together with the observation of an association between cytokines and cognitive disorders in other diseases ( Kronfol and Remick, 2000 , McAfoose and Baune, 2009 ), we hypothesized that innate immune cytokine synthesis in the acute phase of COVID-19 predicts anosognosia scores for memory dysfunction in the chronic phase of COVID-19 (6-9 months). In addition, and in line with known associations between brain structures and inflammatory processes in both Alzheimer’s disease ( Bayat et al, 2022 , Jayaraman et al, 2021 ) and COVID-19 ( Douaud et al, 2022 ), we expected to observe patterns of brain connectivity involving the hippocampal, para-hippocampal and subcortical structures related to inflammatory markers (e.g., TNFα).…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Based on previous results indicating that variation of monocytes to total leukocytes is predictive of anosognosia in the chronic phase (Nuber-Champier, 2022), together with the observation of an association between cytokines and cognitive disorders in other diseases ( Kronfol and Remick, 2000 , McAfoose and Baune, 2009 ), we hypothesized that innate immune cytokine synthesis in the acute phase of COVID-19 predicts anosognosia scores for memory dysfunction in the chronic phase of COVID-19 (6-9 months). In addition, and in line with known associations between brain structures and inflammatory processes in both Alzheimer’s disease ( Bayat et al, 2022 , Jayaraman et al, 2021 ) and COVID-19 ( Douaud et al, 2022 ), we expected to observe patterns of brain connectivity involving the hippocampal, para-hippocampal and subcortical structures related to inflammatory markers (e.g., TNFα).…”
Section: Introductionsupporting
confidence: 58%
“…One emerging hypothesis following observations of persistent long-term cognitive difficulties and physiological patterns after COVID-19 suggests a potential trigger or accelerator of neurodegenerative process ( Beauchet and Allali, 2022 , McAlpine et al, 2021 ). Indeed, different studies have shown that COVID-19 associates with neurotoxicity, hippocampal degeneration, and increased risk of Alzheimer's disease ( Bayat et al, 2022 , Chiricosta et al, 2021 , Li et al, 2022 ). However, although the hypothesis of an initiation (or acceleration) of neurodegenerative cascades is central after COVID-19 infection, other hypotheses that limbic encephalitis after COVID-19 ( Franke et al, 2023 , Franke et al, 2021 ) would result in persistent cognitive symptoms could potentially be another interesting avenue (Shnayder et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Although no viral RNA was isolated, the hippocampus in these studies showed microglial activation, T lymphocyte infiltration, and increases in the levels of interleukins 1 and 6, suggestive of a neuroinflammation cascade, with the result also being recreated in an animal model of SARS-CoV-2 infectionneurovirulence [133]. Furthermore, spatial and architectural changes were noted not only in the neuronal and microglial but also in the astrocytic cellular populations, as well as changes in the cellular morphology [135,136].…”
Section: Hippocampal Damagementioning
confidence: 92%
“…Mahajan and Mason pointed out that the reduction in hippocampal volume could indicate cognitive deficits in memory (Mahajan and Mason, 2021), and this has been reported in COVID-19 patients (Liu et al, 2022). Similarly, decreased neurogeneration due to COVID-19-related neuroinflammation in the hippocampus could result in cognitive decline, including memory loss (Lynch, 2010;Bayat et al, 2022;Radhakrishnan and Kandasamy, 2022). In contrast, a follow-up study looking at both self-report and brain imaging data showed that COVID-19 survivors had significantly greater structural volume and functional activity in the hippocampus bilaterally as compared with healthy controls (Tu et al, 2021).…”
Section: Introductionmentioning
confidence: 93%